A Case for Federal Regulation of Telemedicine in the Wake of the Affordable Care Act - Marino, Bill; Prasad, Roshen; Gupta, Amar (Science and Technology Law Review, 2015)
Telemedicine involves the remote diagnosis and treatment of patients using technology. Its practice has been well received in the United States in recent years. However, its growth remains encumbered by a fragmented, state-based system of licensing telemedicine professionals. This system creates a heavy burden on practitioners, limiting the number of qualified doctors in this space. State-level reforms of this system have been proposed, but only a centralized federal reform effort is likely to effect change. Importantly, it has been argued that such a federal reform effort would not survive constitutional challenges. But in the wake of recent legal challenges to the Affordable Care Act (ACA), this seems not to be the case. Specifically, two responses to the ACA–National Federation of Independent Business v. Sebelius and Liberty University v. Lew—have borne rulings that, together, provide firm constitutional support for federal reform of telemedicine licensure.